The optimization planning of research equipment operation through the efficient integration of research equipment and scientist - Yoon, Donghun (International Journal of Engineering and Technology, 2026)
This paper provides a quantitative way of ensuring the placement and integration of research equipment and scientists. An attempt was made to develop methods of enhancing the research equipment efficiency by focusing on the research equipment utilization difficulty level and the research equipment utilization capability of scientists. Eight research equipment and five scientists were selected for the study. Methods and research results on how to deploy and integrate research equipment and manpower according to the ranks based on the research equipment utilization difficulty and the research capabilities of scientists are presented herein. It is believed that a systematic method of and an optimized plan for deploying and integrating research equipment and scientists, as opposed to the intuitive method, are necessary. That is, deploying and integrating research equipment and scientists according to the ranks based on the research equipment utilization difficulty level and the research equipment utilization capability of the scientists are effective. The authors are confident that an efficient and optimized deployment and integration study for research equipment and scientists will make a significant contribution to research efficiency and productivity improvement. It is hoped that the findings obtained from this study will prove to be very useful for professors, researchers, and policymakers at universities and research institutes around the world.